Nearly one in five essential medicines fail quality standards in Africa: A systematic review and meta-analysis of MNCH medicines and antimalarials - Jean Christophe Rusatira; Manuela Dorado Novoa; Jean Berchmans Uwimana; Cameron Persaud; Eishita Pal; Ayesha Khan; Henry Michtalik; Neelaveni Padayachee; Murray Lumpkin; Charles Preston; Saifuddin Ahmed (PLOS Global Public Health, 2026)
Substandard and falsified (SF) medicines pose a major threat to maternal, newborn, and child health (MNCH) and malaria control in Africa, yet their true burden remains uncertain. We conducted a systematic review and meta-analysis of studies published between 2010 and 2025 that chemically tested the quality of essential MNCH and antimalarial medicines collected in African countries. Following PRISMA 2020 guidelines and a registered PROSPERO protocol, we searched PubMed, Embase, Web of Science, and WHO databases, screened 3,178 records, and included 123 studies from 34 countries reporting on 36,069 medicine samples. Studies were appraised with the MEDQUARG checklist, and random-effects meta-analyses with Freeman–Tukey transformation were used to estimate pooled SF prevalence overall and by therapeutic class, country, and subregion. Meta-regression explored study-level drivers of heterogeneity. Overall, 17.9% (95% CI 13.6–22.7) of tested medicines failed quality standards. Failure rates were highest for corticosteroids (65.0%), uterotonics (43.9%), and hematinics (34.7%); antimalarials, antihypertensives, and antibiotics ranged from 15-20%. Estimates for corticosteroids and hematinics carried wide confidence intervals, reflecting sparse underlying data. Western and Central Africa had the greatest regional burdens, whereas Southern Africa showed lower pooled estimates but with sparse data. Substandard medicines accounted for most poor-quality products (pooled prevalence 12.8%), while falsified medicines were less common (1.2%). Therapeutic category, geographic subregion, and use of mystery-client purchasing were significant predictors of heterogeneity, whereas publication year and methodological quality were not. Nearly one in five essential MNCH and antimalarial medicines tested in Africa are SF, posing a major barrier to reducing preventable maternal, neonatal, and child mortality. Strengthened regulatory systems, risk-based post-market surveillance, and priority attention to high-risk therapeutics, particularly uterotonics and antimalarials, are urgently needed. As the African Medicines Agency becomes operational, this evidence base offers a concrete foundation for directing continental regulatory investment where it is most needed.